Production of Raw Cassava Starch-Digesting Amylase of Streptomyces sp. No.4 by Solid State Fermentation - Dyah Primarini; Yoshiyuka Ohta (Indonesian Food and Nutrition Progress, 1999)
The effect of culture conditions and medium components on raw cassava starch-digesting enzyine production were investigated with Streptomyces sp. No. 4 under solid state fermentation. The enzyme production on a basal solid medium cbmposed of rice or wheat bran as a main component by the strain reached the maximum after 3 days cultivation. The optimum pH, temperature, moisture content of medium for the enzyme production were around 6.0, 35C and 50-60%, respectively. Addition of 12%(w/w) raw cassava starch, 0.24%(w/w)CSL and 20 mM MgS0 4 into those medium improved the enzyme production. The maximum production of the enzyme on improved medium was performed after 4 days cultivation. The main enzymatic products from hydrolysis of raw and gelatinized cassava starch by the enzyme were mainly maltose and maltotriose.